Expression and clinical significance of long non-coding RNA HNF1A-AS1 in human gastric cancer. Issue 1 (December 2015) - Dang, Yuan; Lan, Fenghua; Ouyang, Xiaojuan; Wang, Kai; Lin, Youdong; Yu, Yinghao; Wang, Lie; Wang, Yu; Huang, Qiaojia
Abstract Background Increasing evidence has demonstrated that long non-coding RNAs (lncRNAs) play essential roles in the occurrence and development of human cancers, including gastric cancer (GC). However, the functional and clinical significance of lncRNAs are still poorly understood. Methods In this study, the expression of LncRNA HNF1A antisense RNA 1 (HNF1A-AS1 ) was first examined by lncRNAs microarray analysis in 6 GC tissues, and was then further verified by real-time quantitative reverse transcription PCR (qRT-PCR) both in 3 GC cell lines and 161 cases of GC tissues. We also evaluated the association betweenHNF1A-AS1 expression and clinicopathological features of patients with GC. Results LncRNAs microarray analysis results exhibited thatHNF1A-AS1 was downregulated in GCs tissues (mean fold change 2.06, p  < 0.05), which was further confirmed by qRT-PCR. The results from qRT-PCR showed that the expression ofHNF1A-AS1 was not only downregulated in three GC cell lines (AGS, BGC-823, and MKN-45) relative to that in a normal gastric mucosal epithelial cell line (GES-1), but also decreased in GC tissues relative to that in paired adjacent non-neoplastic tissues (low expression, 94 of 161; low expression rate, 58.38 %). Furthermore, lowHNF1A-AS1 expression was associated with tumor size/diameter (p  = 0.005, multivariate analysis), levels of serum carcinoembryonic antigen (CEA), and carbohydrate antigen 19-9 (CA19-9), and RRM1 expression in tissue samples (p  = 0.028, p  = 0.009, andp  = 0.006, respectively). Conclusions Taken together, our data indicate that lncRNAHNF1A-AS1 may be a regulator of GC, and thus, it may have potential as a novel biomarker and treatment target for this type of cancer.